2017
DOI: 10.1038/s41598-017-07578-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98 negatively regulates myocardial infarction-induced apoptosis by down-regulating Fas and caspase-3

Abstract: Acute myocardial infarction (MI) is the leading cause of sudden death worldwide. MicroRNAs (miRs)is a novel class of regulators of cardiovascular diseases such as MI. This study aimed to explore the role of miR-98 in MI and its underlying mechanisms. We found that miR-98 was downregulated both in infarcted and ischemic myocardium of MI mice as well as H 2 O 2 -treated neonatal rat ventricular myocytes (NRVCs). miR-98 overexpression remarkably increased cell viability and inhibited apoptosis of H 2 O 2 -treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Here, we found a marked reduction in left ventricular end-diastolic posterior wall thickness, ejection fraction, and fractional shortening percentage in Dox-treated rats, concomitantly with increased cardiomyocyte membrane permeability and serum LDH concentration. This was consistent with previous studies in several animal models [8,19,33]. However, upregulation of miR-29b was effective in improving cardiac function.…”
Section: Discussionsupporting
confidence: 83%
“…Here, we found a marked reduction in left ventricular end-diastolic posterior wall thickness, ejection fraction, and fractional shortening percentage in Dox-treated rats, concomitantly with increased cardiomyocyte membrane permeability and serum LDH concentration. This was consistent with previous studies in several animal models [8,19,33]. However, upregulation of miR-29b was effective in improving cardiac function.…”
Section: Discussionsupporting
confidence: 83%
“…Other miRNAs have been shown to crosstalk with MI oxidative stress-related genes. MiR-98 negatively regulates MI by inhibiting Fas/Caspase-3 signal [91]. MiR-370 was shown to have a protective role by inhibiting oxidative stress in cardiac myocytes targeting FOXO1 [92].…”
Section: Mirna and Ros Crosstalk During MImentioning
confidence: 99%
“…They found that miRNA-1 reduced the protein levels of antioxidant enzymes glutamate cysteine ligase (Gclc), SOD1, and glucose-6-phosphate dehydrogenase (G6PD) under oxidative stress conditions [118]. Other miRNAs, such as miRNA-130a [119] and miRNA-98 [120], are investigated to be associated with ROS-related cardiomyocyte apoptosis. MiRNA-208a promoted apoptosis and oxidative stress in the I/R injury rat model by regulation of protein tyrosine phosphatase receptor type G and protein tyrosine phosphatase, non-receptor type 4 [121].…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%